Pregnancy following poliomyelitis. Issue 610 (August 1976) - Daw, E.; Chandler, G.
Abstract : A review of forty-nine pregnancies in thirty-seven patients who had previously suffered from poliomyelitis found that obstetric complications were proportional to the clinical disabilities of the patient. A simple test of unilateral weight-bearing gives a good clue as to whether pelvic asymmetry is present.